The Intersection of Linguistics and Law: Forensic Language Analysis in Judicial Practice - Seffiani Dwi Azmi (PT. AVID MEDIA INDONESIA, 2025)
The growing intersection between linguistics and law has given rise to the development of forensic linguistics as a distinct and impactful field of study. As legal systems increasingly rely on linguistic evidence to resolve disputes, clarify ambiguities, and identify authorship, forensic linguistics plays a crucial role in bridging the gap between language science and judicial practice. This paper explores the theoretical and practical dimensions of forensic linguistics, focusing on its application in judicial contexts such as authorship attribution, discourse analysis, interpretation of legal texts, and the detection of deceptive or manipulative language. Through an integrative analysis of scholarly contributions and real-world case studies, this article argues that forensic linguistics not only enhances the fairness and accuracy of legal processes but also reinforces the democratic principle of access to justice. The findings highlight that effective collaboration between linguists and legal practitioners is essential to maximize the potential of linguistic expertise in addressing complex judicial challenges.